Penerapan Pendekatan Pendidikan Matematika Realistik Berbantuan Autograph untuk Meningkatkan Kemampuan Komunikasi Matematis pada Siswa Kelas VIII SMP - Reggie Angelina; Marojahan Panjaitan (Journal on Education, 2024)
The research carried out was motivated by the low mathematical communication skills of students at SMP Negeri 15 Medan. Based on preliminary data, only 26% of students meet the criteria for sufficient mathematical communication skills. This research aims to find out whether the application of realistic mathematics education assisted by Autograph can improve mathematical communication skills in class VIII junior high school students. The subjects in this research were all students in class VIII-1 of SMP Negeri 15 Medan for the 2023/2024 academic year, totaling 31 students. Meanwhile, the object taken in this research is improving the mathematical communication skills of class VIII students at SMP Negeri 15 Medan for the 2023/2024 academic year after implementing a realistic mathematics education approach. Data collection was carried out using initial tests, observations, and tests of mathematical communication skills. The resulting data was analyzed in three stages, namely data reduction, data exposure, and data conclusion. In this research, researchers also observed the teacher's ability to manage learning and student activities during learning using the PMR approach. The two observation results were analyzed using descriptive statistics. so that it shows that the results of the observations can be categorized into student more active and good groups. Meanwhile, students gave positive responses to implementing this Realistic Mathematics Education Approach. Students' mathematical communication abilities after implementing the realistic mathematics learning approach experienced an increase in the class.